The concept of Umrah DIY / Siti Atikah Rusli, Arni Abdul Gani and Nor Asmalina Mohd Anuar - Rusli, Siti Atikah; Abdul Gani, Arni; Mohd Anuar, Nor Asmalina (Universiti Teknologi MARA Cawangan Kedah, 2023)
The purpose of this paper is to define Umrah DIY. This paper is a systematic review on the concept of Umrah DIY whereby the paper will discuss a newly coined concept for religious travel of a literature study on travel and co- creation value. This research explored a niche segment of travellers who choose not to use travel agents and make their own arrangements to perform Umrah, and with the Saudi Arabia Government's decision that had launched Tourist e-Visa in September 2019, a window of opportunity has opened to perform Umrah DIY trips. The paper provides new insights into the definition of DIY traveller that focuses on religious travel by combining with co- creation value. The findings are not able to be generalized to other DIY conventional travel/tourism markets. Opportunities for future empirical research in the area can be broadened as a basis of developing related religious tourism products and services in Malaysia as well to extend the current literature on religious travel.